The Effect of Green Accounting Practices, Environmental Performance, and Firm Size on Corporate Profitability - Eko Cahyo Mayndarto; Zulkhaedir Abdussamad; Ikhyanuddin; Hakim (Journal Management & Economics Review (JUMPER), 2026)
This study examines the effect of green accounting practices, environmental performance, and firm size on corporate profitability. Amid increasing environmental concerns and regulatory pressures, firms are encouraged to integrate sustainability into their accounting and operational strategies. Using a quantitative explanatory research design, this study analyzes secondary panel data obtained from companies listed on the Indonesia Stock Exchange over the period 2020–2022. Corporate profitability is measured using return on assets, while green accounting practices are assessed through an environmental accounting disclosure index, environmental performance is measured using an environmental rating score, and firm size is proxied by the natural logarithm of total assets. Multiple linear regression analysis is employed to test the proposed hypotheses. The results indicate that green accounting practices have a positive and significant effect on corporate profitability, suggesting that transparent recognition of environmental costs enhances operational efficiency and stakeholder confidence. Environmental performance is also found to positively influence profitability, supporting the view that effective environmental management contributes to financial performance through reduced risk and improved reputation. Furthermore, firm size has a positive and significant effect on profitability, reflecting the role of organizational resources and economies of scale. Overall, the findings demonstrate that sustainability-oriented accounting and environmental practices can serve as strategic tools to enhance corporate profitability and long-term business sustainability.